EFEKTIVITAS KINERJA KEUANGAN DALAM MENENTUKAN MODEL PREDIKSI PEMERINGKATAN SUKUK - Ramadhani, Febrina Nur; Kaluge, David (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2019)
This study aims to analyze the effectiveness of financial performance in determining the prediction model for sukuk. The financial performance used in this study consists of leverage, liquidity, solvency, profitability, productivity and coverage ratio. Tests were carried out on 37 companies whose sukuk were registered with PT PEFINDO rating agencies and had financial statements in 2011-2018 using multiple discriminant analysis (MDA). The results show that financial performance can form a prediction model for sukuk with a model accuracy rate of 89.2%. There are four financial performance variables that can form a prediction model, namely leverage with long term liabilities/total asset proxy, liquidity with the proxy of current assets/current liabilities, profitability with the proxy of operating income/sales, and coverage with proxy operating income/total liabilities.